Brand authenticity versus brand reputation: Automobile sector - Loureiro, S. M. C.; Le Bellego, G. (Proceedings of ANZMAC 2016 - Marketing in a Post-Disciplinary Era, 2016)
The current study aims to analyze the effect of both brand authenticity and brand reputation on brand attachment considering the automotive sector. A sample of 376 participants, members of car brand communities, collaborate in a survey. Findings reveal that the perception of authenticity could be more effective than brand reputation on enhancing brand attachment. However, the effect could depend on the car brand strategy. Limitations and suggestions for further research are also provided.